PENERAPAN RESTORATIVE JUSTICE OLEH KEJAKSAAN NEGERI PASAMAN TERADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Bunga Roswari; Sukmareni Sukmareni; Syaiful Munandar (LPPM Universitas Ekasakti Padang, 2023)
The application of restorative justice by the Pasaman District Prosecutor's Office to perpetrators of criminal acts of narcotics abuse is an approach in the criminal justice system that focuses on restoration, reconciliation and restoration of relationships damaged by criminal acts. The aim of this research is to examine the implementation of restorative justice by the Pasaman District Prosecutor's Office towards perpetrators of criminal acts of narcotics abuse using empirical juridical methods. The results of this research show that restorative justice for perpetrators of narcotics abuse has been implemented but is not optimal because there are still obstacles, based on Attorney General Regulation Number 18 of 2021 which can only be applied to narcotics addicts, narcotics abusers and victims of narcotics abuse, in the event that they are caught or arrested by the police, evidence of usage expires in one day and also the prosecutor must check whether the suspect is the final user (end user), check the suspect's profile in relation to financial transactions and the suspect's way of life (know your suspect), and must meet the requirements of the results The perpetrator's integrated assessment team tested positive for using narcotics. The obstacle faced by the prosecutor's office is because the prosecutor's office is not directly involved in the investigation process, so the prosecutor's office does not yet know whether the perpetrator can actually implement restorative justice or not, whether the perpetrator is really a narcotics addict, whether the evidence has been used up so The prosecutor's office must coordinate between sectors. And the effort to overcome the obstacles is by profiling or mapping, where the prosecutor's office must look at the perpetrator's legal status, user history, to his involvement in using the narcotics